Penilaian Tingkat Kesehatan PT Bank Mandiri (Persero) Tbk Melalui Metode Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC) - Dini Dwi Ermawati; Syafira Nabiila; Herfita Libria ursulawaty (Jurnal Aplikasi Perpajakan, 2025)
The purpose of this study is to analyze the health level of PT Bank Mandiri (Persero) Tbk for the period 2019–2023. The analytical method used in this research is descriptive quantitative analysis. The data employed are secondary data in the form of annual financial reports of PT Bank Mandiri Tbk for the period 2019–2023, obtained from the official website of Bank Mandiri (www.bankmandiri.co.id) as well as official publications from the Financial Services Authority (OJK) (www.ojk.go.id) and Bank Indonesia (BI) (www.bi.go.id). The analytical tool applied is the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital). The results of the study show that the health level of Bank Mandiri, based on the RGEC method, during the period 2019–2023 is in a very healthy condition. The overall average score obtained was 83.33% in 2019 and 2020 (healthy category), increased to 86.67% in 2021 (very healthy category), further rose to 93.33% in 2022 (very healthy category), and slightly decreased to 90% in 2023 but remained in the very healthy category.